Shakhṣīyat Sunan Kalijaga fī taqālīd Mataram al-Islāmīyah - Hamid Nasuhi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2017)
Sunan Kalijaga is one of the Wali (The Saint) who is very popular in Java. His name is increasingly popular because he was mentioned many times in a myriad of chronicles (babad) composed in the Islamic Mataram period, particularly since 17th century. Text written on the chronicles are hagiographic so that enormous things in the current Java, especially in the field of politic, culture, and religious is always cited as the creation of this Wali. The appearance and the story modification of puppet story, Lir-ilir song, bedug usage as salat signal, the legend of tatal (woodchips) in the establishment of the Demak Great Mosque, the sacrad cloth of Antakusuma, and etcetera, is deemed as the Sunan Kalijaga’s legacy. Therefore, he is being regarded as the representation of perfect human in view of the Javanese, not even less perfect than the kings who had ever ruled in Mataram Kingdom.DOI: 10.15408/sdi.v24i1.5222